2014
DOI: 10.1049/iet-cvi.2013.0101
|View full text |Cite
|
Sign up to set email alerts
|

Exact image representation via a number‐theoretic Radon transform

Abstract: This study presents an integer‐only algorithm to exactly recover an image from its discrete projected views that can be computed with the same computational complexity as the fast Fourier transform (FFT). Most discrete transforms for image reconstruction rely on the FFT, via the Fourier slice theorem (FST), in order to compute reconstructions with low‐computational complexity. Consequently, complex arithmetic and floating point representations are needed, the latter of which is susceptible to round‐off errors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 81 publications
(154 reference statements)
0
12
0
Order By: Relevance
“…The versatility of SMILI makes it ideally suited for a range of biomedical studies and has already been successfully utilised for a number of other applications since its release. It has been employed for advanced 3D in vivo visualisation of structures and models in musculoskeletal radiology [28,29], computing and visualising surface distances between models and bone shape [30,31], as well as in recent work on deformation fields in radiotherapy treatment planning [32,33]. The latter has clinical value in not only understanding the effects of…”
Section: Custom Clinical Applicationmentioning
confidence: 99%
“…The versatility of SMILI makes it ideally suited for a range of biomedical studies and has already been successfully utilised for a number of other applications since its release. It has been employed for advanced 3D in vivo visualisation of structures and models in musculoskeletal radiology [28,29], computing and visualising surface distances between models and bone shape [30,31], as well as in recent work on deformation fields in radiotherapy treatment planning [32,33]. The latter has clinical value in not only understanding the effects of…”
Section: Custom Clinical Applicationmentioning
confidence: 99%
“…Since the slices of the DFT, and therefore R(m, t) space, does not require any interpolation, the backprojection requires no interpolation either and so it can be computed as a convolution without any interpolation error. This is referred to as circulant back-projection (CBP), since the result is a superposition of circulant matrices [54]. Adding slices to the DFT is O(µN ), where µ is the total number of measured slices and there are at most N + 1 slices.…”
Section: Finite Iterative Reconstructionmentioning
confidence: 99%
“…3. The solution is to use the Number Theoretic Transform and the Number-Theoretic Radon Transform of Chandra [20].…”
Section: Proposition 4 (Kernel Projections) the Projections Of The 2mentioning
confidence: 99%
“…The resulting NRT was constructed specifically to remedy the loss of precision when forming Finite Ghosts. Chandra [20] also showed that the implementation of the NTT is faster than the DFT because of its integer-only operations.…”
Section: Number Theoretic Convolutionmentioning
confidence: 99%
See 1 more Smart Citation